2020
DOI: 10.1108/ilt-12-2019-0513
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of impact-sliding behavior and fretting wear of tubes against different supports in steam generators

Abstract: Purpose The purpose of this study is to reveal the interaction behavior between tubes and supports in steam generators and study the fretting wear of tubes in different load conditions. Design/methodology/approach The fretting wear tests were conducted to investigate the fretting wear behavior of the tubes against three kinds of supports: the drilled circular holes (DCH), anti-vibration bars (AVBs) and trefoil orifice holes (TOH), which are widely used supports in nuclear steam generators. In this paper, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…1 unidirectional; 2 reciprocating; and 3 multi-mode combination motion. Guo et al (2020aGuo et al ( , 2020b, 2020c) studied the effects of impact angles, excitation forces, clearances, support forms and other factors on the impact-sliding fretting wear and established an energy-based wear model, which is more accurate than the traditional Archard model. However, these studies did not consider the synergism of wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…1 unidirectional; 2 reciprocating; and 3 multi-mode combination motion. Guo et al (2020aGuo et al ( , 2020b, 2020c) studied the effects of impact angles, excitation forces, clearances, support forms and other factors on the impact-sliding fretting wear and established an energy-based wear model, which is more accurate than the traditional Archard model. However, these studies did not consider the synergism of wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the wear degree at 25 °C is less than that at 290 °C, and the wear rate increase with the applied impact load's augmentation. Guo et al [8,9] conducted impact wear test studies to predict the dynamic relationships between impact angle, impact energy loss, and wear degree. Yilmaz et al [10] systematically studied the effect of impact wear cycles on the wear degree and failure mechanism of 316L stainless steel.…”
Section: Introductionmentioning
confidence: 99%